Lower Nitrous Oxide Emissions from Anhydrous Ammonia Application Prior to Soil Freezing in Late Fall Than Spring Pre‐Plant Application. Issue 4 (1st July 2016) - Tenuta, Mario; Gao, Xiaopeng; Flaten, Donald N.; Amiro, Brian D.
Abstract : Fall application of anhydrous ammonia in Manitoba is common but its impact on nitrous oxide (N2 O) emissions is not well known. A 2‐yr study compared application before freeze‐up in late fall to spring pre‐plant application of anhydrous ammonia on nitrous oxide (N2 O) emissions from a clay soil in the Red River Valley, Manitoba. Spring wheat ( Triticum aestivum L.) and corn ( Zea mays L.) were grown on two 4‐ha fields in 2011 and 2012, respectively. Field‐scale flux of N2 O was measured using a flux‐gradient micrometeorological approach. Late fall treatment did not induce N2 O emissions soon after application or in winter likely because soil was frozen. Application time did alter the temporal pattern of emissions with late fall and spring pre‐plant applications significantly increasing median daily N2 O flux at spring thaw and early crop growing season, respectively. The majority of emissions occurred in early growing season resulting in cumulative emissions for the crop year being numerically 33% less for late fall than spring pre‐plant application. Poor yield in the first year with late fall treatment occurred because of weed and volunteer growth with delayed planting. Results show late fall application of anhydrous ammonia before freeze‐up increased N2 O emissions at thaw and decreased emissions for the early growing season compared to spring pre‐plant application. However, improved nitrogen availability of late fall application to crops the following year is required when planting is delayed because of excessive moisture in spring. Core Ideas: Late‐fall ammonia application prior to freeze‐up did not induce N2 O emissions over winter. Late‐fall application did increase N2 O emissions during thaw the following year. Despite lower area‐based emission in the first study year, poor yield increased yield‐scaled emissions. For the second study year, yield‐scaled emissions were similar for application treatments.